The Existence Of State Attorney Prosecutors In Providing Legal Assistance To Government Agencies Related To Land Disputes - Nur’ Andini; Amara Az Zahra Pratiwi; Harmono Harmono; Dadan Taufik Fathurohman (PT Publikasiku Academic Solution, 2024)
The prosecutor's authority does not only focus on prosecution but also includes the civil and state administrative fields, where the prosecutor acts as a State Attorney (JPN). The method used is empirical juridical, which involves direct research in the field related to the duties and functions of the Cirebon City District Attorney's Office in handling land disputes, especially in Case Number: 27/Pdt.G/2023/PN.Cbn. This research aims to reveal the existence of JPNs and their efforts in providing legal assistance as defendants representing government agencies in court. The results show that JPNs play an important role in representing government agencies, especially in the recovery of state assets related to land disputes. The implication of this research is the strengthening of the role of JPNs in legal disputes, which can strengthen efforts to protect state assets by government agencies in the future.